1990
DOI: 10.2337/diacare.13.6.631
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and Atheroma: 20-Yr Perspective

Abstract: Many clinical studies have shown an increased insulin response to oral glucose in patients with ischemia of the heart, lower limbs, or brain. Hyperinsulinemia also occurs in patients with angiographically proved atherosclerosis without ischemia and thus appears to be related to arterial disease and not to be a nonspecific response to tissue injury. Fasting insulin levels and insulin responses to intravenous stimuli, including glucose, tolbutamide, and arginine, are normal, suggesting a gastrointestinal factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
213
0
10

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(225 citation statements)
references
References 134 publications
2
213
0
10
Order By: Relevance
“…On the negative side, results from observational studies have indicated that high levels of endogenous insulin may increase CVD risk [4]. In addition, experimental studies in animals have shown that high exogenous insulin leads to increased atherosclerosis [5]. When high endogenous insulin levels are indeed a CVD risk factor one might expect a paradoxically increased risk of CVD in patients treated with exogenous insulin, as this leads to high (pharmacological) circulating insulin levels [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…On the negative side, results from observational studies have indicated that high levels of endogenous insulin may increase CVD risk [4]. In addition, experimental studies in animals have shown that high exogenous insulin leads to increased atherosclerosis [5]. When high endogenous insulin levels are indeed a CVD risk factor one might expect a paradoxically increased risk of CVD in patients treated with exogenous insulin, as this leads to high (pharmacological) circulating insulin levels [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance is known to affect the physiology of various organs, including skeletal muscles, adipose tissue and liver. Furthermore, recent basic and clinical studies have described the direct effects of insulin resistance at the level of the vessel wall [37][38][39][40] . LpL is known to exist in endothelial cells, showing activity, and LpL was also reported to exist on the coronary lumen surface 41) .…”
Section: Significance Of a Low Preheparin Lpl Mass Concentration In Smentioning
confidence: 99%
“…3 Insulin resistance is often accompanied by elevated concentrations of plasma insulin and abnormalities in lipid and lipoprotein metabolism, such as hypertriglyceridemia and low concentrations of high-density lipoprotein (HDL) cholesterol. 4,5 These metabolic abnormalities may be risk factors for non-insulindependent diabetes mellitus (NIDDM) and coronary heart disease. 6,7 Although there have been many reports showing a linkage between insulin resistance and glucose intolerance in diabetic animals, 8 Kodama et al clearly demonstrated that the linkage between them was not always observed because insulin resistance occurred before the manifestation of hyperglycemia in young db/db mice.…”
Section: Introductionmentioning
confidence: 99%